The Effect of the 7E Cycle Learning Model on Students' Cognitive Learning Outcomes in Biodiversity Material - Annisa Muhaimin Hidayati, Annisa Muhaimin Hidayati; Annisa, Annisa Muhaimin Hidayati (Kirana Publisher (KNPub), 2023)
This study aims to determine the extent to which the learning cycle 7E (Learning Cycle 7E) influences student cognitive learning outcomes in Class X biodiversity material. This type of research was quasi-experimental using a nonequivalent control group design . The research subjects were all class X students in the 2022/2023 semester, a total of 48 students. The research instrument was a cognitive ability test consisting of 20 multiple choice questions taken proportionally to the biology question bank. The data analysis technique used is descriptive analysis to provide an overview of cognitive learning outcomes and inferential analysis to test the research hypothesis based on the results of the descriptive analysis showing that cognitive learning outcomes in the experimental class are higher than the control class with a mean value of 82.5 and the control class 70 , 13. The results of the hypothesis test show that the value of l a i t h i t = 4.54 greater than t t ab = 1.67 which means that there is an influence of the learning cycle 7E model (Learning Cycle 7E) on students' cognitive learning outcomes in class X biodiversity material